Let’s Talk With Let’s Read: Pemanfaatan Aplikasi Cerita Digital Terhadap Keterampilan Berdialog Siswa Kepong, Malaysia - Aulia, Raihanah; Sari, Suci Perwita (Jurnal Gentala Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the Let's Read digital storybook application on the Indonesian language dialogue skills of students at the Kepong Guidance Center (SB), Malaysia. Dialogue skills are an important part of oral language skills because they are related to the ability to convey ideas, respond to interlocutors, and interact actively. The study used a quantitative approach with a quasi-experimental design of the one-group pretest–posttest design. The research subjects were 25 students with a total sampling technique. Data collection used a structured observation instrument containing 15 aspects of statements with 5 indicators of dialogue skills. Data analysis was carried out through descriptive statistics and inferential tests using SPSS including validity, reliability, normality, and paired sample t-test. The results showed that the instrument was valid and highly reliable. Pretest and posttest data were normally distributed and homogeneous. The average score of dialogue skills increased from 36.2 to 48.9. The paired sample t-test showed a significance of 0.000 (<0.05), so the Let's Read application is effective in improving students' dialogue skills and can be an alternative innovative learning media in non-formal education.